Microbial diversity in honeybees - Wick, Charles Harold; Wick, David A. (CRC Press, an imprint of the Taylor & Francis Group, 2021)
"Honeybees are an important link in our food chain because they are major pollinators of food crops. In recent years, honeybee populations have declined precipitously perhaps due to changes in their microbiome. This book describes and identifies the bee microbiome using a proteomics technology. Chapters include the detection and identification of microbes found in honeybees collected around the United States. This book contains new data and illustrates the rich diversity of microbes as collected by honeybees. It is a must read for everyone concerned about the honeybee and working in the industry."--Publisher's website.